An impermeable grouting material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611161168.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
1、解决材料在含水环境中的“浸润与粘结矛盾”问题:即传统憎水性有机浆液无法有效润湿亲水的煤岩和混凝土表面,导致界面粘结失败;而亲水性无机浆液虽能润湿,但其粘结强度和韧性往往不足
1、卓越的两亲性与浸润性:梭形单体作为表面活性剂,大幅降低浆液表面张力,使其既能被水携带深入含水裂隙,又能有效排开水膜,润湿并粘附亲水的煤岩和混凝土表面,解决了传统憎水有机浆材“不粘”的难题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of grouting materials technology, and in particular to an anti-seepage grouting material, its preparation method, and its application. Background Technology
[0002] Coal mine underground water reservoir technology is an important way to achieve mine water protection and utilization. Its safety hinges on the seepage prevention performance of the coal pillar dam and the sealed wall. However, the coal pillar dam itself has a large number of original micro-fissures, and due to the difference in material properties (rigid-plastic) and deformation performance between it and the artificially constructed concrete sealed wall, seepage channels are easily formed at the joint. Conventional pure inorganic (such as cement-based) or pure organic (such as polyurethane, acrylate) grouting materials have obvious limitations in dealing with such complex leakage problems: Cement-based materials: high viscosity, difficult to inject into micro-fissures; long setting time, easily dispersed by water flow; poor adhesion to coal and concrete, poor flexibility, and prone to new cracking under mining stress. Organic chemical grouting materials (such as polyurethane): although they have good permeability, they are highly hydrophobic, making it difficult to effectively spread and wet the fissure surface in water-bearing fissures, resulting in poor encapsulation; insufficient adhesion to the hydrophilic coal and concrete interface; poor durability and anti-aging performance, and high cost. Therefore, developing a new type of grouting material that can efficiently penetrate micro-fractures, firmly bond with hydrophilic coal and concrete, and possess excellent flexibility and durability is key to solving the problem of leakage in underground coal mine reservoirs. Summary of the Invention
[0003] The present invention aims to solve the following technical problems: 1. Solve the problem of "wetting and bonding contradiction" of materials in water-containing environments: that is, traditional hydrophobic organic slurries cannot effectively wet hydrophilic coal, rock and concrete surfaces, resulting in interface bonding failure; while hydrophilic inorganic slurries can wet, but their bonding strength and toughness are often insufficient.
[0004] 2. Solve the problem of "injectability and retention" of micro-cracks: Traditional cement grout is difficult to inject into micron-level cracks due to particle size and viscosity issues; while low-viscosity chemical grout is easily diluted or washed away by water flow after injection, and cannot be effectively retained, gelled and sealed in dynamic water environment.
[0005] 3. Solve the problem of "rigid-flexible" interface compatibility: Coal pillar dam body (plastic body) and concrete sealing wall (rigid body) will undergo differential deformation under mine pressure. Existing rigid grouting materials are prone to cracking, while flexible materials have insufficient strength and cannot simultaneously meet the requirements of long-term sealing strength and deformation adaptability.
[0006] 4. Solving the "compatibility and synergy" problem of simple mixing of organic and inorganic materials: Simple physical blending leads to phase separation, and the interface becomes a performance bottleneck. This invention aims to achieve stable composite and synergistic performance of organic and inorganic phases at the nanoscale / molecular scale, forming a significant synergistic effect.
[0007] This invention provides a seepage-proof grouting material, its preparation method, and its application, suitable for complex seepage environments in underground coal mine reservoirs. The core innovation of this material lies in its molecular design, which introduces a monomer with a unique spindle-shaped structure. This structure acts as a "bridging molecule," with a hydrophilic group at one end, a hydrophobic segment at the other, and a rigid framework in the middle. This achieves uniform composite and synergistic performance of the organic and inorganic phases at the nanoscale, thereby significantly improving the material's wettability, permeability, adhesion, and final seepage-proof effect.
[0008] In a first aspect, the present invention proposes a seepage-proof grouting material, the raw materials of which include component A and component B. Component A includes ultrafine cement, nano-silica, metakaolin, amphiphilic polymer monomers with a spindle structure, and water-soluble epoxy resin; the molecular structure of the amphiphilic polymer monomers includes hydrophilic polymerizable end groups, rigid aromatic skeletons, and hydrophobic long-chain alkyl tails. Component B includes an aqueous amine curing agent, a coagulating accelerator, and a toughening agent.
[0009] Furthermore, the hydrophilic polymerizable end group is an acrylate, methacrylate, vinyl, or epoxy group.
[0010] Furthermore, the rigid aromatic skeleton is one or more benzene rings, biphenyl rings, or naphthalene rings.
[0011] Furthermore, the hydrophobic long-chain alkyl tail is a straight-chain or branched alkane with 8-18 carbon atoms.
[0012] Furthermore, component A also includes water, dispersant, and defoamer.
[0013] Secondly, the present invention provides a method for preparing any of the above-mentioned anti-seepage grouting materials, comprising the following steps: Under stirring conditions, the ultrafine cement, nano-silica and metakaolin are added sequentially to the aqueous solution of the additives and stirred thoroughly to disperse them. The water-soluble epoxy resin is then added to fully integrate it with the inorganic slurry. The amphiphilic polymer monomer is added and stirred evenly. The mixture is then vacuum dried under stirring conditions to obtain the A component slurry. The B component was mixed under stirring conditions and stirred until homogeneous to obtain a B component solution; The A component slurry and the B component solution are mixed and stirred evenly to obtain the grouting material.
[0014] Further, at a stirring speed of 400-600 rpm, 40-60 parts of the ultrafine cement, 3-8 parts of the nano-silica, and 3-8 parts of the metakaolin are added sequentially by mass fraction. After the addition is complete, the stirring speed is 1200-1500 rpm, and the mixture is stirred for 20-40 minutes. At a stirring speed of 600-800 rpm, 5-15 parts of the water-soluble epoxy resin are added, and the mixture is stirred at this speed for 10-15 minutes. At a stirring speed of 400-600 rpm, 1-5 parts of the amphiphilic polymer monomer are added. After the addition is complete, the stirring speed is 800-1000 rpm, and the mixture is stirred for 15-25 minutes. The mixture is then vacuum dried at a stirring speed of 50-100 rpm for 10-20 minutes.
[0015] Further, at a stirring rate of 200-400 rpm, 70-85 parts of the water-based amine curing agent, 5-10 parts of the accelerator and 5-15 parts of the toughening agent are mixed by mass fraction and stirred for 10-15 minutes.
[0016] Further, the A component slurry and the B component solution are mixed at a volume ratio of (3-5):1.
[0017] Thirdly, the present invention proposes the application of any of the above-mentioned anti-seepage grouting materials in the coal pillar dam body or dam body connection of underground water reservoir in coal mines.
[0018] The beneficial effects of this invention are as follows: 1. Excellent amphiphilicity and wettability: As a surfactant, the spindle-shaped monomer significantly reduces the surface tension of the slurry, enabling it to be carried by water deep into water-bearing fissures and effectively dissipate the water film to wet and adhere to hydrophilic coal, rock and concrete surfaces, solving the problem of "non-stickiness" of traditional hydrophobic organic slurry materials.
[0019] 2. Excellent permeability: The composite system has low viscosity due to the dispersion effect of the spindle-shaped monomers, and the nano-SiO2 and ultrafine cement particles are not easy to agglomerate, which can effectively penetrate into the micro-cracks at the millimeter or even micrometer level.
[0020] 3. Strong interfacial adhesion: The hydrophilic end of the spindle-shaped monomer is anchored to the surface of inorganic materials (coal, concrete, cement hydration products) through chemical bonds and physical interactions, while the hydrophobic end is embedded in the polymer (epoxy resin cured network), forming a strong "pinning effect" that greatly enhances the interfacial bonding force and avoids debonding.
[0021] 4. Synergy of flexibility and rigidity: The resulting interpenetrating network structure has both the flexibility of polymer materials, which can adapt to the small deformation of the coal pillar dam, and the rigidity and durability of inorganic materials, with high compressive strength and stable long-term performance.
[0022] 5. Environmental Protection and Economy: This invention primarily uses inorganic materials, reducing costs and environmental impact; water is used as a solvent, making it safe and non-toxic. The anti-seepage grouting material boasts excellent comprehensive performance and is suitable for coal pillar dams or dam connections in underground coal mine reservoirs, improving the construction efficiency of underground coal mine reservoirs.
[0023] 6. The preparation method of this invention achieves chemical bonding at the nano / molecular scale between the organic and inorganic interfaces, ensuring stable compatibility between the two phases. Preferably, by matching the material characteristics with different rotation speeds, the synergistic effect is fully utilized. Detailed Implementation
[0024] The embodiments described below are some, but not all, embodiments of the present invention. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply.
[0025] A seepage-proof grouting material, the raw materials of which include component A and component B.
[0026] Component A includes ultrafine cement, nano-silica, metakaolin, amphiphilic polymer monomers with a spindle-shaped structure, water-soluble epoxy resin, water, dispersant, and defoamer.
[0027] The amphiphilic polymer monomer has a molecular structure comprising a hydrophilic polymerizable end group, a rigid aromatic backbone, and a hydrophobic long-chain alkyl tail. The hydrophilic polymerizable end group can be an acrylate, methacrylate, vinyl, or epoxy group. The rigid aromatic backbone can be one or more benzene rings, biphenyl, or naphthalene rings. The hydrophobic long-chain alkyl tail can be a straight-chain or branched alkane with 8-18 carbon atoms. Specifically, amphiphilic polymer monomers with a spindle-shaped structure may include p-dodecylstyrene (CH2=CH–Ph–(CH2)). 11 CH3; 2-phenoxyethyl methacrylate CH2=C(CH3)–CO–O–CH2-CH2–O–Ph; Bisphenol A dimethacrylate CH2=C(CH3)–CO–O–C(CH3)2–Ph–Ph–O–CO–CH2=C(CH3); Glycidyl phenyl ether O–CH2–CH–O–Ph–(CH2) 11 CH3, etc.
[0028] The structural features of the spindle-shaped monomer molecule are as follows: "Spindle head" - hydrophilic end: acrylate group, providing high reactivity and strong interaction forces (hydrogen bonds, van der Waals forces) with the surface of inorganic materials; "Spindle body" - rigid skeleton: one or more benzene rings, providing molecular rigidity and stability, preventing curling during curing, and ensuring effective "bridging"; "Spindle tail" - hydrophobic end: long-chain alkane (such as dodecyl chain), giving the molecule hydrophobicity, enabling it to be compatible and entangled with the subsequently formed organic polymer network.
[0029] Component B includes water-based amine curing agents, accelerators, and toughening agents.
[0030] The preparation method of the above-mentioned seepage-proof grouting material includes the following steps: 1. Preparation of Component A Slurry 1.1 Under stirring conditions, add 0.1-0.5 parts of defoamer and 0.2-1.0 parts of dispersant to water by mass fraction, stir for 5-10 minutes until completely dissolved, and obtain a uniform aqueous solution of the additive.
[0031] 1.2 Under stirring conditions, add ultrafine cement (preferably with a particle size of D90≤20 μm), nano silica and metakaolin to the aqueous solution of the additives in sequence, and stir and disperse thoroughly until the slurry is uniform and fine, with no visible agglomerates.
[0032] 1.3 Add water-soluble epoxy resin to fully integrate it with the inorganic slurry.
[0033] 1.4 Add an amphiphilic polymer monomer with a spindle-shaped structure, stir until homogeneous, and vacuum dry under stirring conditions to remove air bubbles introduced during stirring, thereby obtaining a uniform, stable, and pumpable slurry of component A.
[0034] The preferred conditions for preparing component A slurry are as follows: At a stirring speed of 400-600 rpm, add 40-60 parts of ultrafine cement, 3-8 parts of nano-silica, and 3-8 parts of metakaolin by mass fraction. After addition, maintain a stirring speed of 1200-1500 rpm for high-speed shear dispersion for 20-40 minutes. High-speed, long-duration shearing pre-constructs a stable inorganic suspension substrate, preventing inorganic particles from agglomerating and settling. Add 5-15 parts of water-soluble epoxy resin at a stirring speed of 600-800 rpm and stir at this speed for 10-15 minutes. Reducing the stirring speed during this process allows the resin to fully wet the surface of the inorganic particles. Add 1-5 parts of amphiphilic polymer monomer at a stirring speed of 400-600 rpm. Gentle stirring during this process allows the hydrophilic ends of the monomer to fully adsorb and bond to the surface of the inorganic hydrated particles, while the hydrophobic segments embed into the epoxy organic network, precisely achieving organic-inorganic interface chemical bonding. After adding the ingredients, stir at 800-1000 rpm for 15-25 minutes. Then vacuum dry at 50-100 rpm for 10-20 minutes.
[0035] 2. Preparation of component B solution Component B is mixed under stirring conditions and stirred until homogeneous to obtain a component B solution. Preferably, 70-85 parts by mass fraction of water-based amine curing agent, 5-10 parts by mass fraction of accelerator and toughening agent are mixed at a stirring rate of 200-400 rpm and stirred for 10-15 minutes.
[0036] 3. Preparation of composite grouting materials Mix component A slurry and component B solution, preferably in a volume ratio of (3-5):1. Stir at high speed for 10-20 minutes to obtain the grouting material.
[0037] The grouting construction process of the grouting material of this invention is as follows: 1. Before construction, the A component slurry and the B component solution are pumped into the static mixer separately using a dual-liquid grouting pump. The volume ratio of the A component slurry to the B component solution can be controlled at (3-5):1, and a more preferred ratio is 4:1.
[0038] 2. The mixed grout is injected into the target fracture through the pre-embedded grouting pipe. The initial grouting pressure should be controlled at 0.5-1.5 MPa, and then gradually adjusted according to pressure changes.
[0039] 3. When the grouting pressure steadily rises to 2.0-2.5 MPa and is maintained for 5-10 minutes, it indicates that the crack has been basically filled and grouting can be stopped.
[0040] Example 1 This embodiment will prepare a standard strength grouting material.
[0041] The preparation method of the seepage-proof grouting material includes the following steps: 1. Preparation of Component A Slurry 1.1 Add water, which accounts for 30% of the total mass of component A, to the reactor. While stirring at 400 rpm, add 0.3% defoamer and 0.6% dispersant to the water in sequence, and stir for 5 minutes to obtain a uniform aqueous solution of the additives.
[0042] 1.2 At a stirring speed of 500 rpm, 50% ultrafine cement (D90≤20 μm), 5% nano silica and 5% metakaolin were slowly added to the aqueous solution of the additives in sequence. Then the stirring speed was increased to 1300 rpm and high-speed shearing was performed for 30 minutes to fully stir and disperse until the slurry was uniform and fine and there were no visible agglomerated particles.
[0043] 1.3 Add 8% water-soluble epoxy resin at a stirring speed of 700 rpm and stir for 12 minutes to fully integrate it with the inorganic slurry.
[0044] 1.4 Add 1.1% p-dodecylstyrene at a stirring speed of 500 rpm, stir at 900 rpm for 20 minutes, and vacuum dry at a stirring speed of 80 rpm for 15 minutes to obtain component A slurry.
[0045] 2. Preparation of component B solution 80% waterborne polyamide curing agent, 8% anhydrous calcium chloride, and 12% polyurethane toughening agent were mixed at a stirring rate of 300 rpm and stirred for 12 minutes to obtain component B solution.
[0046] 3. Preparation of composite grouting materials Mix component A slurry and component B solution at a volume ratio of 4:1 and stir at high speed for 10 minutes to obtain grouting material.
[0047] Example 2 This embodiment will prepare a highly permeable and flexible grouting material.
[0048] The preparation method of the seepage-proof grouting material includes the following steps: 1. Preparation of Component A Slurry 1.1 Add water, which accounts for 35% of the total mass of component A, to the reactor. While stirring at 400 rpm, add 0.3% defoamer and 0.6% dispersant to the water in sequence, and stir for 5 minutes to obtain a uniform aqueous solution of the additives.
[0049] 1.2 Add 45% ultrafine cement (D90≤20 μm), 4% nano silica and 4% metakaolin to the aqueous solution of the additives at a stirring speed of 500 rpm. Then increase the stirring speed to 1400 rpm and perform high-speed shearing for 35 minutes to ensure dispersibility until the slurry is uniform and fine with no visible agglomerates.
[0050] 1.3 Add 7.3% water-soluble epoxy resin at a stirring speed of 800 rpm and stir for 15 minutes to fully integrate it with the inorganic slurry.
[0051] 1.4 Add 3.8% 2-phenoxyethyl methacrylate at a stirring speed of 600 rpm to greatly enhance amphiphilicity and permeability. Stir for 25 minutes and vacuum dry at a stirring speed of 80 rpm for 15 minutes to obtain component A slurry.
[0052] 2. Preparation of component B solution 75% waterborne polyamide curing agent, 5% anhydrous calcium chloride, and 20% polyurethane toughening agent were mixed at a stirring speed of 300 rpm and stirred for 15 minutes to obtain component B solution.
[0053] 3. The preparation process of the composite grouting material is the same as in Example 1.
[0054] Example 3 This embodiment will prepare an early-strength, fast-setting grouting material.
[0055] The preparation method of the seepage-proof grouting material includes the following steps: 1. Preparation of Component A Slurry 1.1 Add water, which accounts for 25% of the total mass of component A, to the reactor. While stirring at 400 rpm, add 0.3% defoamer and 0.6% dispersant to the water in sequence, and stir for 5 minutes to obtain a uniform aqueous solution of the additives.
[0056] 1.2 Add 55% ultrafine cement (D90≤20 μm), 3.5% nano silica and 3.6% metakaolin to the aqueous solution of the additives at a stirring speed of 500 rpm. Then increase the stirring speed to 1200 rpm and shear at high speed for 25 minutes until the slurry is uniform and fine and there are no visible agglomerated particles.
[0057] 1.3 Add 5% water-soluble epoxy resin at a stirring speed of 800 rpm and stir for 15 minutes to fully integrate it with the inorganic slurry.
[0058] 1.4 Add 7% bisphenol A dimethacrylate at a stirring speed of 600 rpm to ensure basic wettability, stir for 15 minutes, and then vacuum dry at a stirring speed of 80 rpm for 15 minutes to obtain component A slurry.
[0059] 2. Preparation of component B solution 70% waterborne polyamide curing agent, 25% anhydrous calcium chloride, and 5% polyurethane toughening agent were mixed at a stirring speed of 300 rpm and stirred for 15 minutes to obtain component B solution.
[0060] 3. Preparation of composite grouting materials Mix component A slurry and component B solution at a volume ratio of 3.5:1 and stir at high speed for 10 minutes to obtain grouting material.
[0061] The grouting materials prepared in Examples 1-3 were tested according to standard methods and compared with traditional cement grout. The results are shown in Table 1.
[0062] Table 1
[0063] 1. Example 1 (Standard Strength Type): All properties are well-balanced with no weaknesses. Its strength, adhesion, and flexibility are significantly superior to traditional cement grout, making it suitable for most general seepage prevention and plugging scenarios.
[0064] 2. Example 2 (High-permeability and flexible type): By increasing the proportion of spindle-shaped monomers and toughening agents, it exhibits the best permeability (lowest viscosity) and wettability (minimum contact angle), while also possessing the highest bond strength and flexibility (elongation at break). This is the best choice for solving leakage at micro-cracks and deformed joints.
[0065] 3. Example 3 (early strength and fast setting type): Through high inorganic content, low water-cement ratio and high efficiency accelerator, the fastest gelation speed and the highest compressive strength are achieved, which is suitable for emergency leak plugging scenarios with water inrush or requiring rapid load-bearing.
[0066] In summary, the grouting material provided by this invention can be designed and optimized within a wide range by adjusting the formula, thereby specifically solving leakage problems of underground water reservoirs in coal mines with different characteristics (such as micro-cracks, large flow rates, pressurized water, and deformation joints), and its comprehensive performance is far superior to that of traditional materials.
[0067] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A seepage-proof grouting material, characterized in that, The raw materials include component A and component B. Component A includes ultrafine cement, nano-silica, metakaolin, amphiphilic polymer monomers with a spindle structure, and water-soluble epoxy resin. The molecular structure of the amphiphilic polymer monomer includes hydrophilic polymerizable end groups, a rigid aromatic backbone, and a hydrophobic long-chain alkyl tail. Component B includes an aqueous amine curing agent, a coagulating accelerator, and a toughening agent.
2. The seepage-proof grouting material according to claim 1, characterized in that, The hydrophilic polymerizable end group is an acrylate, methacrylate, vinyl, or epoxy group.
3. The seepage-proof grouting material according to claim 1, characterized in that, The rigid aromatic skeleton is one or more benzene rings, biphenyl rings, or naphthalene rings.
4. The seepage-proof grouting material according to claim 1, characterized in that, The hydrophobic long-chain alkyl tail is a straight-chain or branched alkane with 8-18 carbon atoms.
5. The seepage-proof grouting material according to claim 1, characterized in that, Component A also includes water, dispersant, and defoamer.
6. The method for preparing the seepage-proof grouting material according to any one of claims 1-5, characterized in that, Includes the following steps: Under stirring conditions, the ultrafine cement, nano-silica and metakaolin are added sequentially to the aqueous solution of the additives and stirred thoroughly to disperse them. The water-soluble epoxy resin is then added to fully integrate it with the inorganic slurry. The amphiphilic polymer monomer is added and stirred evenly. The mixture is then vacuum dried under stirring conditions to obtain the A component slurry. The B component was mixed under stirring conditions and stirred until homogeneous to obtain a B component solution; The A component slurry and the B component solution are mixed and stirred evenly to obtain the grouting material.
7. The method for preparing the seepage-proof grouting material according to claim 6, characterized in that, At a stirring speed of 400-600 rpm, add 40-60 parts of the ultrafine cement, 3-8 parts of the nano-silica, and 3-8 parts of the metakaolin by mass fraction. After the addition is complete, stir at 1200-1500 rpm for 20-40 minutes. Then, add 5-15 parts of the water-soluble epoxy resin at a stirring speed of 600-800 rpm and stir at this speed for 10-15 minutes. Add 1-5 parts of the amphiphilic polymer monomer at a stirring speed of 400-600 rpm. After the addition is complete, stir at a stirring speed of 800-1000 rpm for 15-25 minutes. Then, vacuum dry at a stirring speed of 50-100 rpm for 10-20 minutes.
8. The method for preparing the seepage-proof grouting material according to claim 6, characterized in that, At a stirring rate of 200-400 rpm, mix 70-85 parts by mass fraction of the water-based amine curing agent, 5-10 parts by mass fraction of the accelerator and the toughening agent, and stir for 10-15 minutes.
9. The method for preparing the seepage-proof grouting material according to claim 6, characterized in that, The A component slurry and the B component solution are mixed at a volume ratio of (3-5):
1.
10. The application of the anti-seepage grouting material according to any one of claims 1-5 in the coal pillar dam body or dam body connection of underground water reservoir in coal mines.
